Nutrition and growth - Martorell, Reynaldo; Haschke, Ferdinand (Lippincott Williams & Wilkins, 2001)
A collection of papers presented at a workshop that focused on nutrition and growth and nutrition disorders and growth disorders in children. Intended for professional public.
Nestlé Nutrition Workshop Series. Pediatric Program ; Volume 47
Keywords: vývoj dítěte; poruchy výživy kojenců; Growth Disorders; fyziologie výživy dětí; pediatrie; poruchy růstu; Child Development; Infant Nutrition Disorders; Developmental Disabilities; Child Nutritional Physiological Phenomena; nutriční poruchy u dětí; vývojové poruchy u dětí; nutriční terapie, dietoterapie a výživa; Child Nutrition Disorders